Quasi Z-source NPC inverter for PV application - Effah, Francis Boafo; Wheeler, Patrick; Watson, Alan James; Clare, Jon C. (2017)
This paper presents the operating principles and modified space vector modulation strategy for a three-phase quasi Z-source neutral point clamped inverter for solar photovoltaic applications. This topology combines the advantages of the neutral point clamped and quasi Z-source inverters. These advantages include single-stage buck-boost power conversion, continuous input current, and low voltage stress of switches. Simulation results are presented to verify the presented concepts.